Avaliação da atividade antifúngica in vitro do α-pineno sobre Candida spp. isoladas de pacientes com otomicose - Nobrega, Jefferson Rodrigues (2019)
Fungi stand out among infectious diseases due to the increased incidence and rates of morbidity and mortality. These microorganisms are generally opportunistic in nature, capable of developing various infections, including otomycosis. This is an infection caused by filamentous and/or yeast fungi that affects the auditory system. The main etiological agents involved in otomycosis are species belonging to the genera Aspergillus and Candida. Treatment of this infection involves elimination of risk factors, debris removal, use of antiseptic and/or antifungal drugs. However, the increased number of otomycosis cases, the small number of antifungal agents available, the use of antiseptic substances without proven safety, and the increase of resistant fungal strains have aroused researcher’s interest in the search for alternative therapies, especially for derivatives of plants and their metabolites, which stands out the monoterpene αpinene. The objective of this work was to evaluate the antifungal activity of α-pinene against Candida species isolated from otomycosis, by means of in vitro assays for the determination of Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC) and evaluation of micromorphological alterations in the presence of the phytoconstituent, as well as investigating the effect of the association between monoterpene and boric acid, using the Checkerboard technique. The α-pinene showed significant antifungal activity against the strains tested, with superior inhibitory activity against C. parapsilosis species. In addition, MFC against strains C. albicans and C. parapsilosis characterized fungicidal monoterpene. α-Pinene has also been shown to be effective in inhibiting the onset of fungal structures, such as pseudohifas, and causing a marked decrease in blastoconidia. Finally, the study of association between phytoconstituent and boric acid produced additive effects, the best results being observed on the strains of C. parapsilosis. However, although synergic results were not evidenced in this study, it is important to note that antagonistic results were not produced in any of the combinations performed. The data obtained in the present study provide clearer expectations for future pharmacological studies, besides highlighting the importance of αpinene as a remarkable antifungal compound and stimulating successive researches in order to enable its insertion into traditional therapeutics, optimizing pharmacological strategies against otomycosis.